From Discovery to the Future Medical Applications of Venom-derived Analgesic Peptides for the Treatment of Peripheral Pains - Bagheri-Ziari, Sedigheh; Bagheri, Kamran Pooshang (Current Pharmaceutical Design, 2025)
Despite the availability of current peripheral pain medications, patients continue to experience acute pain and often need more potent analgesic options. As a result, the discovery of novel molecules is of significant importance. In recent years, the functional properties of peptides have opened new possibilities for pain treatment. This review explores the peptides derived from venoms that target peripheral pain pathways, while briefly investigating the peptides involved in the pathophysiology of peripheral pain. Key peripheral pain receptors include transient receptor potential vanilloid 1 and 2 (TRPV1 and TRPV2), voltage-gated calcium (Ca++), sodium (Na+), and potassium (K+) channels, as well as acid-sensing ion channels (ASICs). Venoms have shown remarkable potential as a source of new therapeutic molecules. Among venomous creatures, cone snails, snakes, sea anemones, tarantulas, scorpions, and spiders are known to possess analgesic peptides. These peptides exert their pain-relieving effects by influencing ion channels and other receptors. Recent studies have investigated the mechanisms of peptides isolated from venoms in various types of pain. These peptides exhibit robust analgesic effects in animal models. This study demonstrates that analgesic peptides derived from venom effectively reduce peripheral pain intensity, presenting promising new molecules for potential medical applications in peripheral pain management.
Keywords: ion channels